Advanced Nurse Practitioners' (Emergency) perceptions of their role, positionality and professional identity: A narrative inquiry. (23rd February 2020) - Kerr, Lisa; Macaskill, Ann
Abstract: Aims: To explore Advanced Nurse Practitioners' (ANP) (Emergency) perceptions of their role, positionality and professional identity. Background: Advanced nursing practice was formally established in the Republic of Ireland in 2001 with 336 ANPs currently registered, projection increasing to a critical mass of 750 by 2021. Advanced practitioners (Emergency) give full emergency care for a specific cohort of clients with unscheduled, undifferentiated and undiagnosed conditions. Design: Qualitative narrative inquiry using Bourdieu's concepts of habitus, field and capital as the theoretical framework was undertaken. Methods: Data were collected in 10 in‐depth interviews and thematic analysis applied. Results: Five key themes emerged: participants' career pathways, personal and professional transitions, role dimensions and core concepts, and position in the organization and emergent professional identity. Role transitioning and a change in habitus, field and capital revealed the uniqueness of their nursing role. Minimizing waiting times, timely patient care and patient satisfaction were key performance indicators. A heightened awareness regarding higher‐level decision‐making, autonomy and accountability is integral to advanced practice. Conclusion: This study presents unique insights into the ANP role covering recruitment, organizational culture changes required and support to ease transition emerged. Impact: Better understanding the motivation to undertake the role, the transition experience and use of advanced practice skills sets will inform the targets for the future recruitment and retention of ANPs are met nationally and internationally. Dissatisfaction with previous management roles and wanting to be clinically close to patients were motivations to follow an advanced practice clinical career trajectory. Positionality and emergent professional identity are key enablers ensuring that advanced practitioners' roles demonstrate the attributes of advanced practice. Educators could use the findings to develop recruitment, retention and progression strategies. Disseminating the role and scopes of practice could positively influence collaborative models of service delivery and policy development. Abstract : 目的: 研究高级执业护士(急诊部)对其角色、定位和职业认同的认知。 背景: 爱尔兰共和国于2001年正式发布高级护理实践, 目前共注册了336名高级执业护士, 预计到2021年人数将增加至750名。高级执业医师(急诊部)为一组计划外、未分化和未确诊的情况的特殊病人提供全面的急诊护理。 设计: 采用布迪厄的惯习、场域和资本概念为理论框架开展定性叙事研究。 方法: 通过10次深入访谈和专题分析来收集数据资料。 结果: 共出现了五大关键主题:参与者的职涯路径、个人和职业转变、角色维度和核心概念, 以及在组织中的地位和自发职业认同。角色转换和惯习、场域、资本的变化揭示了护理角色具备独特性。尽可能缩短等待时间、及时的患者护理以及患者满意度为关键绩效指标。提高对更高级别决策、自主性和问责制的认识是构成高级实践的一部分。 结论: 本研究对高级执业护士职业角色提出了独特的见解, 内容涵盖了招聘、所需的组织文化变革以及对缓和转变的支持。 影响: 更深入地了解承担这一角色的动机、转变经验和使用高级实践技能, 将在国家和国际层面为今后实现招聘和留用高级执业护士的目标提供信息。对先前管理角色的不满, 并希望临床上接近患者是遵循高级临床实践职业轨迹的驱动因素。 定位和自发职业认同是确保高级执业人员角色展示高级实践特征的关键推动因素。教育工作者可利用研究发现结果来制定招聘、留用和晋升战略。传播实践的作用和范围可对提供服务和政策制定的协作模式产生积极影响。